(3GdHQUGf hGdYQLGf hGdYejGf hGdMhdGfs - (3YeQh Hf HMQ Hf eMHhH GdcfGfj HGdhdGA, GddjKj, CHh YKeGf, GdLGMX,J (B255 (3g` s
(3ChdgG (B:s
(3hgH Gddg dc MSf GdSJeGY hbO NaJ Cf Jchf eSCdJc EjGi cJGHG ai JSejI GdYQLGf GdHQUGf hGdYejGf hGdMhdGf , ef GdHGH GdPi fgjJc Yfg hRgJc ajg , hPcQJ di cJGH GdgjKe Hf YOi ai Pdc s
(3BNQgG (B:s
(3hef MOjK MaUI HfJ YeQ (B: (3Cf GdfHi Udi Gddg Ydjg hSde cGf EPG Chi Edi aQGTI JhSO jOg Gdjefi , hbGd (B:(3QH bfi YPGHc jhe JHYK YHGOc s
(3GdfSNI HgG MhGTs
(3HChdgG YOI JedjcGJs
(3hHBNQgG Jedjc hHgG eTgG HYV GdESJOQGcGJs
(3hai JQjH HYV ChQGbgG EVWQGH s
(3hai BNQgG UaMJGf ai GdYejGf GdCTQGa , GdYhQ , GdMhdGf , GdRQb , hGdabe ddgjKe Hf YOi s
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdCOHs